Strategic Management "Strategic Analysis at PT. Bukit Asam Tbk." - Imandy Yustine Wiyono; Werner R. Murhadi (Dinasti International Journal of Education Management and Social Science, 2025)
The purpose of this study is to analyze the strategy of PT. Bukit Asam Tbk in facing the challenges of the climate crisis, global coal price fluctuations, mining industry competition, and national and international energy transition policies. This study uses a descriptive qualitative approach with a focus on strategy formulation, where analysis is conducted on the company's internal and external environments. Data are obtained from the company's annual report, government regulations, and related secondary sources. The results of the internal and external environmental analysis produce the strengths, weaknesses, opportunities, and threats (SWOT) of PT Bukit Asam Tbk. The SWOT analysis is then entered into a strategy matrix such as External Factor Evaluation (EFE), Internal Factor Evaluation (IFE), Porter's Five Forces, SPACE Matrix, BCG Matrix, IE Matrix, Grand Strategy Matrix (GSM), and Quantitative Strategic Planning Matrix (QSPM). The final strategic recommendation obtained is that PT. Bukit Asam Tbk's strategic choice is product development with diversification into renewable energy, domestic market expansion considering the still large domestic market potential.